Polish Catholic Press. A Bibliographical and Informational Review - Evelina Kristanova (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The author’s intention was to recall the definition, genesis and development of the Polish Catholic press in various historical and political periods by reviewing the available literature on the subject. The emergence of Catholic-oriented periodicals in Poland dates back to the first half of the 19th century during the partitions, while significant development took place after the Second Polish Republic regained independence. The first years of the People’s Republic of Poland were characterised by illusory democratic freedoms, which is why new Catholic periodicals were established. An important turning point came in 1953, when almost all periodicals published by the Catholic Church were closed. Between 1953 and 1956, the editorship of Tygodnik Powszechny was taken over by the PAX Association, which collaborated with the Communist authorities, with the aim of dividing Catholic circles. During the political thaw, some titles were reinstated, although their content was still subject to strict censorship. The democratic changes of 1989 brought in the free market, which in turn became a financial challenge for Catholic editorial boards. Due to a lack of funds, the longstanding Przegląd Powszechny ceased its publications in 2012. The article is an informative and bibliographical review and shows the correlation between the development of the press and changing political conditions. The analysis results in a fragmentary study of the selected press segment.